Penerapan Pembelajaran Kooperatif Tipe Numbered Head Together untuk Meningkatkan Hasil Belajar Siswa pada Pelajaran IPA di Kelas IV-A MIN 1 Yogyakarta - Waridah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study was to determine student learning outcomes before applying Numbered Head Together, testing the application of Numbered Head Together method to improve student learning outcomes knowing student learning outcomes after using Numbered Head Together, and analyzing the comparison of student learning outcomes between before and after applied cooperative learning methods Numbered Head Together type. The research method used is Class Action Research. The findings of this study that by applying cooperative learning the Numbered Head Together type has a positive influence in improving student learning outcomes which are characterized by an increase in student learning outcomes from Pre-Cycle I with an average value of 83.45 and cycle II an average value of 90.00. Between Cycle I and Cycle II, there was an increase of 7.85%. Based on the research that has been done in Cycle I and Cycle II with cooperative learning Numbered Head Together type have increased. The limitations of this study were only carried out in the Lessons on the Science of Energy-Saving Energy Content of Alternative Energy Materials for Students of Class IVA MIN 1 Yogyakarta and not yet comprehensive. Further research is expected to be carried out in all classes.